Fully Revealing Income Measurement - Demski, Joel S.; David E. M. Sappington (The Accounting Review, 1990)
[This article provides a link between two conflicting approaches to accounting theory. One approach focuses on "proper" income measurement or asset valuation. Under this approach, income is often viewed as economic income plus error, where the error arises from institutional constraints. The other approach focuses on information disclosure. According to this other approach, income is generally viewed as an informative random variable that assists in deriving, say, an economic valuation of the entity. The former approach tends to view the economic norm as a desideratum, thereby leaving the demand for accounting services outside of the formal theory. The latter approach tends to view the information content as a desideratum, thereby leaving most accounting structure outside of the formal theory. These two approaches are linked in this article by treating income measurement as a process by which useful information is conveyed, using the language of proper income measurement or asset valuation. Why this particular language is adopted is not addressed. Thus, the question of why one might select a particular measurement scale (e.g., Celsius) over some other scale (e.g., Fahrenheit) is not examined. Rather, the question asked is whether there is any loss of generality by confining the accounting system to income measurement techniques. The answer is no. The argument runs as follows. First, an exogenous stream of net cash flows and realizations of some (informative) random variable are postulated. Then, an accounting system is introduced. At periodic intervals, this system must compute the expected present value of the future net cash flows from (only) the realized net cash flow and random variable. The accounting system then reports the net cash flow and income (defined to be the sum of net cash flow and the change in expected present value) in each period. Finally, it is determined whether reporting net cash flows and income in this manner discloses fully the information contained in the original stream of net cash flows and realizations of the random variable. This may be the case. If not, a conservative accounting treatment can always be constructed that does disclose the information fully. Hence, the accounting apparatus, coupled with conservatism, provides the link between the two approaches to accounting theory. The information content of the accounting measure is ensured even when the measure is computed in a classical manner. A key feature of the argument is that "accounting value" and "economic value" may diverge. Paradoxically, this divergence may be essential to conveying the information. Therefore, it may not be correct to claim that inability to value particular resources or transactions is the important feature in defining the accounting domain.]